Strokes in the anterior circulation: comparison between bridging and intravenous thrombolysis. (27th October 2014) - Sztajzel, R. F.; Muller, H.; Sekoranja, L.; Viaccoz, A.; Mendez Pereira, V.; Narata, A. P.; Lovblad, K.; Altrichter, S.; Michel, P.
<x xml:space="preserve">Abstract</x> Background and purpose To compare safety and efficacy of bridging approach with intravenous (IV) thrombolysis in patients with acute anterior strokes and proximal occlusions. Patients and methods Consecutive patients with ischemic anterior strokes admitted within a 4 h 30 min window in two different centers were included. The first center performed IV therapy (alteplase 0.6 mg/kg) during 30 min and, in absence of clinical improvement, mechanical thrombectomy with flow restoration using a Solitaire stent (StS); the second carried out IV thrombolysis (alteplase 0.9 mg/kg) alone. Only T, M1 or M2 occlusions present on CT angiography were considered. Endpoints were clinical outcome and mortality at 3 months. Results There were 63 patients in the bridging and 163 in the IV group. No significant differences regarding baseline characteristics were observed. At 3 months, 46% (n = 29) of the patients treated in the combined and 23% (n = 38) of those treated in the IV group had a modified Rankin scale (mRS) of 0–1 (P < 0.001). A statistical significant difference was observed for all sites of occlusion. In a logistic regression model, National Institute of Health Stroke Scale (NIHSS) and bridging therapy were independent predictors of good outcome (respectively, P = 0.001 and P = 0.0018). Symptomatic hemorrhage was documented in 6.3% vs 3.7% in the bridging and in the IV group, respectively (P = 0.32). There was no difference in mortality. Conclusions Our results suggest that patients treated with a bridging approach were more likely to have minimal or no deficit at all at 3 months as compared to the IV treated group.